Penambatan Molekuler Penghambatan Aktivitas Enzim α-Amilase dan α-Glukosidase oleh Senyawa Aktif Daun Kirinyuh (Chromolaena odorata L.): Molecular Docking for Inhibition of α-Amylase and α-Glucosidase Enzyme Activities by Active Compounds of Kirinyuh Leaves (Chromolaena odorata L.) - Nelson Gaspersz; Matthew Adi Honey Amos; Sitti Hardiyanti Kalauw; Indrid Harjuni; Mario R. Sohilait (Chemistry Department, Mathematics and Natural Science Faculty, Tadulako University, 2022)
An in silico study was conducted to inhibit the active compound in Kirinyuh leaves (Chromolaena odorata L.) against α-amylase and α-glucosidase enzymes using a molecular docking approach. The docking was carried out on 19 active compounds that had been identified in Kirinyuh leaves and were optimized using the PM3 method. The best results in inhibit on of the α-amylase enzyme were shown by compounds from the flavanone group, namely genkwanin and sakuranetin with binding affinities of -8.3 kcal/mol and -8.1 kcal/mol, respectively, while the best results in inhibiting on of the α-glucosidase enzyme were shown by two compounds from the hydroxybenzoic acid group, namely p-coumaric acid and p-hydroxybenzoic acid with bond affinities of -5.7 kcal.mol and -5.5 kcal.mol, respectively. The interaction between α-amylase with genkwanin and sakuranetin produces one conventional hydrogen bond GLU 233 and GLN 63 respectively. The interaction between α-glucosidase with p-coumaric acid and p-hydroxybenzoic acid produces three conventional hydrogen bonds, HIS 112; GLN 182; ASP 352 and GU 277; GLN 279; ASP 352.